Man’s confrontation with reality: sentient intelligence, directed will and affected feeling in Xavier Zubiri. - Carrera Umaña, Randall (2021)
This research starts with the thesis that in the Xavier Zubiri’s anthropology the human visualization as an animal in realities is of vital importance. This aspect involves the deep study of the three fundamental categories in this author’s philosophy: the sentient intelligence, the affecting feeling, and the tending will. These categories not only evince a clear continuity with the animal feel, but also a particular modulation of the human reality. The integral study of these notions will allow the elucidation of new scenarios of   interpretation of the Zubirian anthropology.